Optimizing the E-Docu Web System to Improve the Performance of BKPSDM Surabaya City Government - Wibisono, Alvito Dimas (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This research aims to determine the contribution of the e-Docu web system to the efficiency of the performance of the Personnel and Human Resources Development Agency (BKPSDM) of the Surabaya City government. As is known, the E-Docu system is used to manage personnel documents. From transfer requests, incoming letters, outgoing letters, documents for accepting honorary staff, as well as other personnel-related documents. Descriptive qualitative methods were used in this research, by collecting data through interviews, observation and analysis of related documents. Through this research, the results were obtained that the e-Docu system was able to increase work efficiency and speed up the management of personnel documents.